2020
DOI: 10.5334/sta.669
|View full text |Cite
|
Sign up to set email alerts
|

‘The Swarm Principle’: A Sub-National Spatial Analysis of Aid Targeting and Donor Coordination in Sub-Saharan Africa

Abstract: Do bilateral and multilateral foreign aid donors target poverty? To answer that question, we present a framework for assessing the quality of aid targeting subnationally. If donors cluster aid in areas with concentrated poverty, or spread out aid in areas of diffuse poverty, then we conclude that donors are targeting aid well. Furthermore, because co-financing may be a mechanism that improves coordination and information-sharing among donors, we examine whether the frequency of donor co-financing increases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Jablonski (2014), cited above, also finds that WB and AfDB aid projects are allocated to areas in Kenya that share the ethnic identity of the president, a conclusion also reached by Briggs (2014). Another study found that the quality of bilateral and multilateral aid targeting varies across countries, with some countries having higher quality targeting of aid on need than others (Findley and Marineau 2016).…”
Section: Literature Reviewmentioning
confidence: 80%
See 1 more Smart Citation
“…Jablonski (2014), cited above, also finds that WB and AfDB aid projects are allocated to areas in Kenya that share the ethnic identity of the president, a conclusion also reached by Briggs (2014). Another study found that the quality of bilateral and multilateral aid targeting varies across countries, with some countries having higher quality targeting of aid on need than others (Findley and Marineau 2016).…”
Section: Literature Reviewmentioning
confidence: 80%
“…Thus it is not clear how the project funds are allocated among the project locations. To avoid losing a considerable amount of the aid information in the dataset, this project follows the precedent set by previous studies of sub-national aid allocation (Öhler andNunnenkamp 2013, Findley andMarineau 2016) by using project locations. Map 1 below shows the distribution of county projects within Uganda.…”
Section: The Independent Variablementioning
confidence: 99%
“…While donors may wish to exert control over when, where, and how resources are allocated, recipients may seek to capture those flows to advance their own political or economic goals (Milner et al, 2016). A raft of studies has examined these dynamics in a subnational setting (Briggs, 2017; Jung, 2020; Marineau & Findley, 2020; Reinsberg & Dellepiane, 2021; Song et al, 2021), often finding that donor aims for when, where, or how resources should be directed may be ultimately frustrated and that aid does not reach the recipients or fulfill the purpose intended by the donor.…”
Section: Introductionmentioning
confidence: 99%